Acculturized English: A Case of Language Hybridization - Naromal-Allen, Nancy (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The rise of English as a prestige language across the globe compellingly attracts many non-natives to use English as medium for the formal arena. In the field of literature, especially in Asia, the so-called non-native English writings have emerged as a result of user preference for what is established and highly esteemed. Since English has its own innate linguistic features from both its own culture and logic, the non-native English users have created strategies to minimize the ’foreignness’ of English by nativizing it: that is, by blending indigenous features of the mother tongue with English. These techniques include code switching, borrowing, embedding, contextualizing, and using syntactic devices consistent with local style. In effect, the accommodation process produces a hybrid English variety representing the version of the non native English user, the so-called "acculturized English", our generic label for all English variants. With hybridization as a bridging ladder to domesticate what is foreign, non native writing in English is actually vigorously drawing up a paradigm of nativization whereby English usage contextualizes itself as it merges with local culture.